Female role stereotypes in print advertising: Identifying associations with magazine and product categories - Zotos, Yorgos; Plakoyiannaki, Emmanuella (My University, 2009)
Purpose – The purpose of this study is three-fold: to provide recent evidence in the UK on the frequency of appearance of female role portrayals in print advertisements; to compare female role stereotypes across magazine types; and to explore the interface between female role stereotypes and product categories. Design/methodology/approach – An integrative approach to content analysis was used in order to analyze advertising communication in print media. The sample consisted of n ¼ 3,830 advertisements published in ten high circulation UK magazines. Findings – The study indicates that women in UK magazine advertisements are mainly portrayed in decorative roles; and that female role stereotypes vary significantly across magazine types. The findings also suggest that there is an association between product categories and female role stereotypes. Practical implications – The study highlights the need for the advertising industry in the UK to adjust its communication practices to the changing role of women in society. Originality/value – The study extends research in the area of female role stereotypes in print advertising by considering the frequency of female role portrayals across different magazine types; and investigating the association between product categories and female role stereotypes.
Keywords: Advertising; Magazines; Women; Prejudice; Sexual discrimination; United Kingdom